Study of Indonesian marriage law on inner marriage practices in the Bidaah drama series - Wiwin, Wiwin; B, Herman; Phireri, Phireri; Syahril, Muh. Akbar Fhad (Priviet Social Sciences Journal, 2026)
In Indonesian law, marriage is a physical and spiritual bond between men and women who aim to form a happy family based on trust in God Almighty. The heresy drama series display inner marriage practice, namely the marriage process that emphasizes the spiritual aspect without fulfilling formal requirements in the form of a marriage guardian, witness human beings, and ijab valid acceptance. Research​ This use method study law normative with approach legislation and analysis draft law marriage in Indonesia. The study results show that inner marriage in the Bidaah series is done through unilateral declaration and claiming spiritual validity, with God as the guardian and angels as witnesses. This is contradictory to Article 1 of the Law of Marriage, which regulates marriage as a physical and spiritual bond that must fulfil the conditions of formal law. In addition, the practice of inner marriage also violates Islamic law, as stated in the Compilation of Islamic Law (KHI), which requires the existence of guardians, witnesses, and clear acceptance of consent to ensure a legitimate marriage. Thus, the practice of inner marriage, as displayed in the series No fulfil terms and conditions marriage as arranged in law positive Indonesia, renders the marriage void ab initio.